The role of zakat during pandemic crisis and post recovery (maqāsid al-sharīʽah perspective) - Haron, Razali; Abdullah Othman, Anwar Hasan; Ashurov, Sharofiddin (IGI Global, 2021)
The Covid-19 pandemic suddenly claimed its existence with thousands of fatalities reported worldwide in just a few months. It has caused great concern and panic resulting to total halt in all activities particularly the economic sector. The lockdown has caused global economic contraction which has led to forecasted economic recession for the year 2020. Islamic social financing sees this phenomenon as an increase in the numbers of the needy and something has to be done. In Islamic social financing certain instruments have been identified as tools to mitigate the turmoil facing people who are badly affected by the pandemic. Zakat, sadaqah, qard al-hasan and infaq can play significant roles especially in providing financial aids to the needy. Zakat in particular has the potential to ease the financial situations for its huge collection recorded. This study employed the document analysis approach to examine the possible role zakat can play during and after the turbulence caused by the pandemic. The findings from the analyses revealed that Islamic social financing via its instruments like zakat, sadaqah, infaq and qard al-hasan are able to offer and provide financial assistance during and post crisis, in this case the Covid-19 pandemic in various sectors like the education, social and humanitarian as well as in the medical sector. The responsible party should continue to provide efficient and hassle free channel for zakat payers to continue paying zakat as it does help in providing sufficient funds and also eradicate poverty in a community that may be caused by any crises alike. The effective and efficient distribution programs are also equally important in ensuring the objective of zakat is achieved in helping the needy.